Comparison of the effectiveness of schema therapy and imago therapy on fear of marriage and attitudes about romance and mate selection in girls - Fereydonpour , Zeynab; Kalhour , Safora; Mohseni , Fatemeh; Namjoo , Farhad (Applied Family Therapy Journal (AFTJ), 2020)
Aim: The purpose of the present study was to determine the effectiveness of schema therapy and imago therapy on the fear of marriage and attitudes about romance and mate selection in girls. Method: The sample was purposefully selected from single female students of Tehran universities. With a public call to participate in the study, 44 single female students were asked about the attitude-choosing questionnaire of Cobb, Larson, & Watson (2003) and fear of marriage Samiei, Yousefi, and Neshat Doost (2013) answered that 36 girls were selected from among them and randomly replaced in two experimental groups: schema therapy (12 girls), experimental group, immunotherapy (12 girls) and control group (12 girls). Both experimental groups underwent the intervention of Young, Klosko & Weishaar (2003) Schema Therapy for 8 90-minute sessions, and Hendrix Imagotherapy (2008), and the control group did not receive any intervention. Data were analyzed using repeated-measures analysis of variance. Results: Results showed that the effect of schema therapy intervention on spouse choice (F= 29.75, P= 0.001) and fear of marriage (F= 12.14, P= 0.004) and imagotherapy intervention on spouse choice (F= 28.51, P = 0.002) and on fear of marriage (F= 14.48, P= 0.003) and this effect was sustained at follow-up. Conclusion: The results of the present study provide evidence that schema therapy and imago therapy are appropriate methods for reducing the fear of marriage and attitude toward spouse selection.